Model Problem Based Learning berbantuan video berita: Pengaruhnya terhadap kemampuan berpikir kritis pada siswa SMA - Fetricia Fetricia; Hadi Soekamto; Djoko Soelistijo; Dwiyono Hari Utomo (Universitas Negeri Malang, 2023)
Critical thinking skills are important for students to solve problems in daily life. The PBL model assisted by news based on video is one of the learning models that in accordance with the demands of curriculum 2013 to improve student's critical thinking skills. This study aims to determine whether or not there is an effect of the PBL model assisted by news based on video for critical thinking skills of high school students. This research is a quasi-experiment by applying a post-test only control group design. The subjects in this study amounted to 66 peoples. Dataa analysis using independentt sample t-test with test results known to be 0.023 less than 0.05, then H0 is rejected and H1 is accepted. The results show that there is an effect of the PBL model assisted by news based on video on the critical thinking skills of high school students. Researchers also compared the average scores of critical thinking skills tests by gender. The resultss showed that the average score of female students was higher than the male students. The reason is the cognitive abilities, problem solving and motivation of female studentss are higher than male students. Kemampuan berpikir kritis penting dimiliki siswa untuk menyelesaikan masalah di kehidupan sehari-hari. Model PBL berbantuan video berita merupakan salah satu model pembelajaran yang sesuai dengan tuntutan kurikulum 2013 untuk meningkatkan kemampuan berpikir kritis siswa. Penelitian ini bertujuan untuk mengetahui ada atau tidak ada pengaruh model PBL berbantuan video berita terhadap kemampuan berpikir kritis siswa SMA. Penelitian ini merupakan eksperimen semu dengan menerapkan post-test only control group design. Subjek dalam penelitian ini berjumlah 66 orang. Analisis dataa menggunakan independentt sample t-test dengan hasil pengujian diketahui 0,023 kurang dari 0,05 maka H0 ditolak dan H1 diterima. Hasil menunjukkan bahwa terdapat pengaruh model PBL berbantuan video berita terhadap kemampuan berpikir kritis siswa SMA. Peneliti juga membandingkan nilai rata-rata tes kemampuan berpikir kritis berdasarkan gender. Hasil menunjukkan bahwa nilai rata-rata siswa perempuan lebih tinggi dibandingkan siswa laki-laki. Penyebabnya yaitu kemampuan kognitif, pemecahan masalah dan motivasi siswaa perempuan lebih tinggii dibandingkan siswa laki-laki.